System design of a hydrogen-powered fuel cell for all-terrain vehicles (ATVs) - Fawad Rahim Malik, 1990-, author 610836; Azhar Abdul Aziz, 1959-, supervisor 378745; Fakulti Kejuruteraan Mekanikal 8081 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Thesis (Sarjana Sains (Kejuruteraan Mekanikal))